Composite fiber textile fabric and preparation method thereof
By using composite fiber textile fabrics with nylon, modified polyester cotton fibers and island fibers, combined with corona treatment, sodium hydroxide solution immersion, hydrogel precursor solution immersion, photocatalyst hydrosol dipping and electrostatic spraying of self-cleaning powder, the existing fabrics are solved, and efficient antibacterial, self-cleaning and durability are achieved.
Patent Information
- Application Number
- CN202411668943.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
AI Technical Summary
Existing composite fiber textile fabrics have shortcomings in antibacterial and purification effects, which are difficult to meet the needs of improving personal hygiene and extending service life, especially in the face of diverse infectious diseases and specific environmental conditions.
The composite fiber textile fabric consisting of nylon, modified polyester cotton fibers and island fibers is used, and is processed through specific preparation methods and processes, including corona treatment, sodium hydroxide solution immersion, hydrogel precursor solution immersion, photocatalyst hydrosol dipping and electrostatic spraying of self-cleaning powder, improving the antibacterial, self-cleaning and durability of the fabric.
It realizes the high antibacterial properties and self-cleaning properties of textile fabrics, can maintain good results after multiple washes, and has good waterproofness, breathability and heat insulation properties, suitable for diverse environmental conditions.
Smart Images

Figure CN119593127A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile fabrics, and in particular to a composite fiber textile fabric and a preparation method thereof. Background Art
[0002] Composite fiber is a kind of multi-component fiber, which is a term for artificial fiber varieties. There are two or more unmixed polymer fibers on the same fiber cross section. This kind of fiber is called composite fiber. It is a physically modified fiber developed in the 1960s. The composite fiber manufacturing technology can obtain two-component fibers with the characteristics of two polymers. There are parallel type, skin-core type, island type and other composite fibers, and the fiber cross section is round and special-shaped. The fiber has three-dimensional curling, high fluffiness and coverage, good conductivity, antistatic and flame retardancy. Composite fiber needs to be spun by a composite spinning machine with a special structure. It is mainly used for wool, blankets, wool fabrics, warm wadding fillings, silk fabrics, non-woven fabrics, medical and sanitary products and special work clothes.
[0003] With the emergence of diverse infectious diseases, enhancing the antibacterial and purification effects of fabrics is of great significance for improving personal hygiene, reducing disease transmission, extending the service life of textiles, and adapting to specific environments (such as medical care, military, outdoor activities, etc.). Summary of the invention
[0004] In order to solve the above problems, the present invention provides a composite fiber textile fabric and a preparation method thereof.
[0005] A composite fiber textile fabric, comprising the following components by mass percentage:
[0006] Nylon: 60-80%;
[0007] Composite fiber: balance;
[0008] The composite fiber is composed of modified polyester-cotton fiber and sea-island fiber in a mass ratio of 1:0.4-0.6.
[0009] Furthermore, the preparation method of the modified polyester-cotton fiber is:
[0010] The polyester-cotton fiber is immersed in a hydrogel precursor solution at a solid-liquid ratio of 1g:40-60mL, and the air pressure is reduced to 70-75kPa by vacuuming. The hydrogel precursor solution is heated to 85-95°C and maintained for 30-40min, and then the surface of the polyester-cotton fiber is subjected to corona treatment, wherein the irradiation temperature of the corona treatment is 20-40°C, the voltage is 15-25kV, the treatment time is 5-15min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 0.5-4.5mm. After the corona treatment is completed, the polyester-cotton fiber obtained by the corona treatment is immersed in a sodium hydroxide solution with a mass fraction of 10-20% at a solid-liquid ratio of 1g:20-30mL, and the air pressure is further reduced to 10-20kPa by vacuuming. After maintaining for 5-10min, the polyester-cotton fiber is taken out and dried to obtain the modified polyester-cotton fiber.
[0011] Description: Vacuum conditions help to remove the air inside the fiber, making it easier for the hydrogel precursor solution to penetrate into the fiber, thereby improving permeability. By controlling the vacuum and heating conditions, the interfacial bonding between the fiber and the hydrogel precursor solution can be optimized to form a more uniform and firm composite material; corona treatment can introduce hydrophilic groups such as carboxyl and hydroxyl groups on the fiber surface. These groups increase the surface energy of the fiber, thereby improving the hydrophilicity. Through corona treatment, the electrostatic half-life of the fiber surface is significantly reduced, improving the antistatic performance; alkaline solution can soften the fiber surface, increase the affinity between the cellulose solution and the polyester-cotton fiber, help the cellulose solution to better penetrate and adhere to the fiber, and form a more uniform and stable hydrogel layer on the fiber surface, which helps to improve the morphology and microstructure of the final composite material.
[0012] Furthermore, the hydrogel precursor solution comprises, by weight, 15 to 20 parts of cellulose solution, 5 to 10 parts of antibacterial agent, 3 to 5 parts of nano zinc oxide and 8 to 10 parts of octadecanethiol.
[0013] Description: Cellulose solution can enhance the mechanical strength and toughness of fabrics, while octadecyl mercaptan, as a surfactant, helps to improve the interface bonding between fiber and hydrogel precursor, further improving the mechanical properties of the composite material; the presence of antibacterial agent and nano zinc oxide provides antibacterial properties for fabrics. Nano zinc oxide can effectively kill bacteria and fungi due to its high specific surface area and photocatalytic activity, enhancing the hygienic safety of fabrics.
[0014] Furthermore, the antibacterial agent is a silver ion antibacterial agent or a guanidine antibacterial agent, and the particle size of the nano zinc oxide is 40 to 50 nm.
[0015] Description: Silver ion antibacterial agents have high wash resistance, and their antibacterial properties can remain good even after multiple washings; guanidine antibacterial agents are compatible with a variety of fabric materials and are suitable for different textile processing processes.
[0016] A method for preparing a composite fiber textile fabric as described in any one of the above, comprising the following steps:
[0017] S1. Using the composite fiber as the core yarn and the nylon as the outer covering yarn in proportion to obtain a blended yarn, using the blended yarn as the warp and weft, and weaving the blended yarn to obtain a woven fabric at a warp density of 580 to 600 yarns / 10 cm and a weft density of 220 to 240 yarns / 10 cm;
[0018] S2, dyeing the woven fabric and then setting it at 165-175° C. to obtain a set fabric;
[0019] S3, padding the blank fabric twice in a photocatalyst hydrosol, performing a UV treatment in the first padding, the temperature of the photocatalyst hydrosol is 25-55°C, the rolling rate is 65-85%, the UV power is 500-600mW, and the second padding is performed in coordination with ultrasonic oscillation, the temperature of the photocatalyst hydrosol is 25-55°C, the rolling rate is 90-100%, and the ultrasonic oscillation frequency is 50-60KHz, to obtain a padded fabric;
[0020] S4, drying and shaping the padded fabric at 100-115° C. for 5-10 min to obtain a textile fabric.
[0021] Furthermore, the photocatalyst hydrosol is a nano titanium dioxide aqueous solution with a concentration of 6 to 9 mg / L, wherein the particle size of the nano titanium dioxide is 5 to 10 nm.
[0022] Description: Nano titanium dioxide has excellent ultraviolet absorption and reflection capabilities, which can greatly improve the anti-ultraviolet function of fabrics and protect the skin from UV radiation damage. Under light conditions, nano titanium dioxide photocatalyst can decompose organic pollutants on the surface of fabrics, such as oil and dust, to achieve a self-cleaning effect.
[0023] Further, after the padded fabric is obtained, electrostatic spraying of self-cleaning powder is performed from one side of the padded fabric toward the other side of the padded fabric, and the electrostatic spraying method is:
[0024] First, spray the first layer on the padding fabric, the spray width of the first layer accounts for 1 / 8 to 1 / 6 of the overall width of the padding fabric, and the length is the same as the overall length of the padding fabric, and then start from 20 to 30% of the width of the first layer, continue to spray the second layer, and then start from 20 to 30% of the width of the second layer, spray the third layer, until the entire padding fabric is sprayed;
[0025] The spraying area of each layer is the same, and after each layer is sprayed, the sprayed padding surface is first heat treated at 100-120° C. for 20-30 minutes;
[0026] In the electrostatic spraying, the distance between the spray gun and the impregnated fabric is 200-250 mm, the voltage is 60-70 kV, the current is 55-65 μA, the compressed air pressure is 0.2-0.4 MPa, and the spraying thickness is 45-65 μm.
[0027] Description: The multi-layer overlapping structure can provide better protection and reduce the wear of the fabric surface caused by friction. The multi-layer overlapping structure helps to disperse external forces, reduce the damage to the fabric caused by scratches, and increase the roughness of the fabric surface, which helps to capture and remove dust particles, thereby improving self-cleaning ability; electrostatic spraying technology can ensure that the powder is firmly attached to the fabric surface and provide a durable coating. Heat treatment is performed after each layer of spraying, which helps the chemical bonding between the powder coating and the impregnated fabric, thereby enhancing the adhesion of the coating and preventing peeling. Heat treatment can eliminate stress inside the coating and improve the mechanical properties of the coating, such as elasticity, toughness and impact resistance.
[0028] Furthermore, the self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder and silane coupling agent in a mass ratio of 1:0.4:0.2-0.3.
[0029] Description: Tourmaline negative ion powder can release negative ions, which have the ability to absorb and decompose harmful substances in the air, helping to keep the fabric clean. Polycarbonate powder provides good mechanical properties, while silane coupling agent can improve the bonding between tourmaline and polycarbonate, and improve the wear resistance and chemical resistance of the overall coating. Silane coupling agent, as a surface modifier, can improve the dispersibility and adhesion of tourmaline powder in polycarbonate powder, ensuring the stability of the coating.
[0030] Compared with the existing composite fiber textile fabrics, the present invention has the following beneficial effects:
[0031] (1) The textile fabric of the present invention is composed of nylon, modified polyester-cotton fiber and sea-island fiber. The high strength and wear resistance of nylon and modified polyester-cotton fiber make the fabric have better durability and tear resistance, and can still maintain good antibacterial and self-cleaning properties even after repeated washing. The fine structure of the sea-island fiber and the appropriate textile process can make the fabric have good waterproofness and breathability, while providing heat insulation and warmth retention effects. The sea-island fiber has high wear resistance and strength, can withstand a certain degree of washing and use, and maintain good appearance and performance. In addition, the sea-island fiber has natural antibacterial properties and can effectively prevent the growth of bacteria and mold.
[0032] (2) In the process of padding the textile fabric of the present invention, the first padding is combined with ultraviolet treatment. The photocatalyst in the photocatalyst hydrosol can generate highly active free radicals under ultraviolet irradiation, has strong oxidizing properties, can effectively decompose organic pollutants and bacteria in the air, and improve the self-cleaning and antibacterial properties of the fabric; the second padding is combined with ultrasonic vibration treatment. The ultrasonic vibration treatment can promote the uniform distribution of the photocatalyst hydrosol on the surface of the fabric, reduce coating defects, and improve the uniformity and adhesion of the coating, thereby enhancing the photocatalytic activity and stability of the fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a comparison chart of the results of investigation 1 of the textile fabric of the present invention;
[0034] Figure 2 It is a comparison chart of the results of the investigation 2 of the textile fabric of the present invention;
[0035] Figure 3 It is a comparison chart of the results of the investigation 3 of the textile fabric of the present invention;
[0036] Figure 4 It is a partial diagram of the electrostatic spraying of the present invention. DETAILED DESCRIPTION
[0037] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0038] Embodiment 1: A composite fiber textile fabric, comprising the following components by mass percentage:
[0039] Nylon: 70%;
[0040] Composite fiber: balance;
[0041] The composite fiber is composed of modified polyester-cotton fiber and sea-island fiber in a mass ratio of 1:0.5;
[0042] The preparation method of the modified polyester-cotton fiber is:
[0043] The polyester-cotton fiber is immersed in a hydrogel precursor solution at a solid-liquid ratio of 1g:50mL, and the air pressure is reduced to 72kPa by vacuumizing. The hydrogel precursor solution is heated to 90°C and maintained for 35min, and then the surface of the polyester-cotton fiber is subjected to corona treatment, wherein the irradiation temperature of the corona treatment is 30°C, the voltage is 20kV, the treatment time is 10min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 2mm; after the corona treatment, the polyester-cotton fiber obtained by the corona treatment is immersed in a sodium hydroxide solution with a mass fraction of 15% at a solid-liquid ratio of 1g:25mL, and the air pressure is further reduced to 15kPa by vacuumizing. After maintaining for 8min, the polyester-cotton fiber is taken out and dried at 70°C to obtain a modified polyester-cotton fiber;
[0044] The hydrogel precursor solution comprises, by weight, 18 parts of cellulose solution, 8 parts of antibacterial agent, 4 parts of nano zinc oxide and 9 parts of octadecanethiol, wherein the antibacterial agent is a silver ion antibacterial agent, and the particle size of the nano zinc oxide is 43-47 nm.
[0045] Embodiment 2: The method for preparing the composite fiber textile fabric as described in Embodiment 1 comprises the following steps:
[0046] S1. Using the composite fiber as the core yarn and the nylon as the outer covering yarn in proportion to obtain a blended yarn, using the blended yarn as the warp and weft, and weaving the blended yarn at a warp density of 590 yarns / 10 cm and a weft density of 230 yarns / 10 cm to obtain a woven fabric;
[0047] S2, dyeing the woven fabric and then setting it at 170° C. to obtain a set fabric; wherein the dyeing is to immerse the woven fabric in a dyeing vat filled with PC dye for 45 minutes;
[0048] S3, the blank fabric is dipped twice in a photocatalyst hydrosol, the first dip is coordinated with ultraviolet treatment, the temperature of the photocatalyst hydrosol is 40°C, the rolling rate is 70%, the ultraviolet power is 550mW, and the second dip is coordinated with ultrasonic oscillation treatment, the temperature of the photocatalyst hydrosol is 40°C, the rolling rate is 95%, and the ultrasonic oscillation frequency is 55KHz, to obtain a dipped fabric; the photocatalyst hydrosol is a nano titanium dioxide aqueous solution with a concentration of 7.5mg / L, wherein the particle size of the nano titanium dioxide is 6-8nm;
[0049] S4, drying and shaping the padded fabric at 112° C. for 8 min to obtain a textile fabric.
[0050] Example 3: This example is different from Example 1 in that a composite fiber textile fabric comprises the following components by mass percentage: nylon: 60%; composite fiber: the remainder; the composite fiber is composed of modified polyester-cotton fiber and sea island fiber in a mass ratio of 1:0.4.
[0051] Example 4: This example is different from Example 1 in that a composite fiber textile fabric comprises the following components by mass percentage: nylon: 80%; composite fiber: the remainder; the composite fiber is composed of modified polyester-cotton fiber and sea island fiber in a mass ratio of 1:0.6.
[0052] Example 5: This example is different from Example 1 in that the polyester-cotton fiber is immersed in the hydrogel precursor solution at a solid-liquid ratio of 1 g:40 mL, the air pressure is reduced to 70 kPa by vacuum, and the hydrogel precursor solution is heated to 85°C and maintained for 30 min.
[0053] Example 6: This example is different from Example 1 in that the polyester-cotton fiber is immersed in the hydrogel precursor solution at a solid-liquid ratio of 1 g:60 mL, the air pressure is reduced to 75 kPa by vacuum, and the hydrogel precursor solution is heated to 95°C and maintained for 40 min.
[0054] Example 7: This example is different from Example 1 in that the irradiation temperature of the corona treatment is 20°C, the voltage is 15 kV, the treatment time is 5 min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 0.5 mm.
[0055] Example 8: This example is different from Example 1 in that the irradiation temperature of the corona treatment is 20°C, the voltage is 25 kV, the treatment time is 15 min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 4.5 mm.
[0056] Example 9: This example is different from Example 1 in that the polyester-cotton fiber obtained by corona treatment is immersed in a 10% sodium hydroxide solution with a solid-liquid ratio of 1 g:20 mL, and the vacuum is continued to reduce the air pressure to 10 kPa and maintained for 5 minutes.
[0057] Example 10: This example is different from Example 1 in that the polyester-cotton fiber obtained by corona treatment is immersed in a 20% sodium hydroxide solution with a solid-liquid ratio of 1 g:30 mL, and the vacuum is continued to reduce the air pressure to 20 kPa and maintained for 10 minutes.
[0058] Example 11: This example is different from Example 1 in that the hydrogel precursor solution comprises, by weight, 15 parts of cellulose solution, 10 parts of antibacterial agent, 5 parts of nano zinc oxide and 10 parts of octadecanethiol.
[0059] Example 12: This example is different from Example 1 in that the hydrogel precursor solution comprises, by weight, 20 parts of cellulose solution, 5 parts of antibacterial agent, 3 parts of nano zinc oxide and 8 parts of octadecanethiol.
[0060] Example 13: This example is different from Example 1 in that the antibacterial agent is a silver ion antibacterial agent, and the particle size of the nano zinc oxide is 40 to 43 nm.
[0061] Example 14: This example is different from Example 1 in that the antibacterial agent is a guanidine antibacterial agent, and the particle size of the nano zinc oxide is 47 to 50 nm.
[0062] Example 15: This example is different from Example 2 in that the warp density is 580 strands / 10 cm and the weft density is 220 strands / 10 cm.
[0063] Example 16: This example is different from Example 2 in that the warp density is 600 strands / 10 cm and the weft density is 240 strands / 10 cm.
[0064] Example 17: This example is different from Example 2 in that the woven fabric is dyed and then set at 165°C to obtain a set fabric.
[0065] Example 18: This example is different from Example 2 in that the woven fabric is dyed and then set at 175°C to obtain a set fabric.
[0066] Example 19: This example is different from Example 2 in that ultraviolet treatment is used in conjunction with the one-time rolling, the temperature of the photocatalyst hydrosol is 25°C, the rolling rate is 65%, and the ultraviolet power is 500mW.
[0067] Example 20: This example is different from Example 2 in that ultraviolet treatment is used in conjunction with the one-time rolling, the photocatalyst hydrosol temperature is 55°C, the rolling rate is 85%, and the ultraviolet power is 600mW.
[0068] Example 21: This example is different from Example 2 in that the second dipping and rolling is performed in coordination with ultrasonic oscillation treatment, the temperature of the photocatalyst hydrosol is 25°C, the rolling rate is 90%, and the ultrasonic oscillation frequency is 50KHz.
[0069] Example 22: This example is different from Example 2 in that the second dipping and rolling is performed in coordination with ultrasonic oscillation treatment, the temperature of the photocatalyst hydrosol is 55°C, the rolling rate is 100%, and the ultrasonic oscillation frequency is 60KHz.
[0070] Example 23: This example is different from Example 2 in that the photocatalyst aqueous sol is a nano-titanium dioxide aqueous solution with a concentration of 6 mg / L, wherein the particle size of the nano-titanium dioxide is 8 to 10 nm.
[0071] Example 24: This example is different from Example 2 in that the photocatalyst aqueous sol is a nano-titanium dioxide aqueous solution with a concentration of 9 mg / L, wherein the particle size of the nano-titanium dioxide is 5 to 6 nm.
[0072] Example 25: This example differs from Example 2 in that the rolled fabric is dried and shaped at 100°C for 5 minutes to obtain a textile fabric.
[0073] Example 26: This example differs from Example 2 in that the rolled fabric is dried and shaped at 115°C for 10 minutes to obtain a textile fabric.
[0074] Example 27: This example is different from Example 2 in that, after obtaining the padded fabric, electrostatic spraying of self-cleaning powder is performed from one side of the padded fabric toward the other side of the padded fabric, and the electrostatic spraying method is:
[0075] like Figure 4 As shown, the spraying width of the first layer accounts for 1 / 7 of the overall width of the padded fabric, and the length is the same as the overall length of the padded fabric. Then, starting from 25% of the width of the first layer, the second layer is sprayed, and then starting from 25% of the width of the second layer, the third layer is sprayed until the entire padded fabric is sprayed.
[0076] The spraying area of each layer is the same, and after each layer is sprayed, the sprayed padding fabric is first heat treated at 110° C. for 25 minutes;
[0077] In the electrostatic spraying, the distance between the spray gun and the padding surface is 225 mm, the voltage is 65 kV, the current is 60 μA, the compressed air pressure is 0.3 MPa, and the spraying thickness is 50 μm;
[0078] The self-cleaning powder consists of tourmaline negative ion powder, polycarbonate powder and silane coupling agent in a mass ratio of 1:0.4:0.25.
[0079] Example 28: The difference between this example and Example 27 is that the spraying width of the first layer accounts for 1 / 8 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Starting from 20% of the width of the first layer, the second layer is sprayed, and starting from 20% of the width of the second layer, the third layer is sprayed until the entire impregnated fabric is sprayed.
[0080] Example 29: The difference between this example and Example 27 is that the spraying width of the first layer accounts for 1 / 6 of the overall width of the impregnated fabric, and the length is the same as the overall length of the impregnated fabric. Starting from 30% of the width of the first layer, the second layer is sprayed, and starting from 30% of the width of the second layer, the third layer is sprayed until the entire impregnated fabric is sprayed.
[0081] Example 30: This example differs from Example 27 in that after each layer of spraying is completed, the sprayed and impregnated fabric is first heat treated at 100°C for 20 minutes.
[0082] Example 31: This example is different from Example 27 in that after each layer of spraying is completed, the sprayed and impregnated fabric is first heat treated at 120°C for 30 minutes.
[0083] Example 32: The difference between this example and Example 27 is that, in the electrostatic spraying, the distance between the spray gun and the dipped fabric is 200 mm, the voltage is 60 kV, the current is 55 μA, the compressed air pressure is 0.2 MPa, and the spraying thickness is 65 μm.
[0084] Example 33: The difference between this example and Example 27 is that, in the electrostatic spraying, the distance between the spray gun and the dipped fabric is 250 mm, the voltage is 70 kV, the current is 65 μA, the compressed air pressure is 0.4 MPa, and the spraying thickness is 45 μm.
[0085] Example 34: This example is different from Example 27 in that the self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder and silane coupling agent in a mass ratio of 1:0.4:0.2.
[0086] Example 35: This example is different from Example 27 in that the self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder and silane coupling agent in a mass ratio of 1:0.4:0.3.
[0087] Experimental Example: The description of this experimental example is based on the scheme described in Example 2, and is intended to illustrate the practical application effect of the present invention.
[0088] In order to explore the antibacterial properties and washing fastness of the textile fabric prepared by the present invention, the test was carried out with reference to GB / T20944.3-2008. Staphylococcus aureus was used as the antibacterial test bacteria to observe its antibacterial property, and the test sample was subjected to 300 standard washes to observe its washing fastness, that is, the antibacterial property after washing.
[0089] 1. To explore the effects of the component ratio of textile fabrics and the preparation parameters of modified polyester-cotton fibers on the antibacterial rate and washing fastness of textile fabrics.
[0090] The difference between the comparative example 1 and the example 1 is that no corona treatment is performed;
[0091] Depend on Figure 1 The results show that the antibacterial rate of the control example 1 lacking corona treatment is significantly lower than that of the examples 1, 3 to 14, so the corona treatment has a certain effect on improving the antibacterial rate and washing fastness of the textile fabric;
[0092] By comparing Examples 1 and 3 to 14, it can be seen that the antibacterial rate and washing fastness of textile fabrics will be reduced if the proportion of nylon is too small or too large, the parameters of the polyester-cotton fiber immersed in the hydrogel precursor solution are too small or too large, the parameters of the corona treatment are too small or too large, the parameters of the polyester-cotton fiber immersed in the sodium hydroxide solution are too small or too large, the proportion of the cellulose solution in the hydrogel precursor is too small or too large, and the particle size of nano zinc oxide is too small or too large. Therefore, in comprehensive comparison, the parameter effect of Example 1 is relatively better.
[0093] 2. Investigate the effects of the component ratio of textile fabrics and the preparation parameters of modified polyester-cotton fibers on the antibacterial rate and washing fastness of textile fabrics.
[0094] The difference between the comparative example 2 and the example 2 is that the ultraviolet radiation is eliminated during the first padding;
[0095] The difference between Comparative Example 3 and Example 2 is that the ultrasonic oscillation treatment is eliminated during the secondary padding;
[0096] Depend on Figure 2 The results show that the control example 2 lacks ultraviolet irradiation, and the control example 3 lacks ultrasonic vibration treatment. Compared with the examples 2 and 15 to 26, the antibacterial rates are significantly reduced. Therefore, the synergistic ultraviolet and ultrasonic vibration treatment during padding has a certain effect on improving the antibacterial rate and washing fastness of textile fabrics.
[0097] By comparing Examples 2 and 15 to 26, it can be seen that the warp and weft density is too small or too large, the blank setting parameters are too small or too large, the parameters of the first impregnation are too small or too large, the parameters of the second impregnation are too small or too large, and the parameters of the photocatalyst hydrosol are too small or too large, which will reduce the antibacterial rate and water fastness of the textile fabric. Therefore, in comprehensive comparison, the parameter effect of Example 2 is relatively better.
[0098] 2. Investigate the effects of the component ratio of textile fabrics and the preparation parameters of modified polyester-cotton fibers on the antibacterial rate and washing fastness of textile fabrics.
[0099] The difference between Control Example 4 and Example 27 is that only one layer of self-cleaning powder is sprayed on the entire padding fabric;
[0100] Depend on Figure 3 As a result, the antibacterial rate and washing fastness of the textile fabrics in Examples 27 to 35 are improved compared with those in Example 2. The control example 4 lacks a laminated structure of self-cleaning powder, and the antibacterial rate and washing fastness of the textile fabrics are reduced compared with Examples 27 to 35. Therefore, the spraying laminated structure of the self-cleaning powder has a certain effect on improving the antibacterial rate and washing fastness of the textile fabrics.
[0101] By comparing Examples 27 to 35, it can be seen that overlapping area that is too small or too large, heat treatment parameters that are too small, electrostatic spraying parameters that are too small or too large, and the proportion of tourmaline negative ion powder in the self-cleaning powder that is too small or too large will reduce the antibacterial rate and water fastness of textile fabrics. In Example 31, the heat treatment temperature is higher and the treatment time is longer, and the performance is improved compared to Example 27, but the improvement is small. Therefore, from an economic point of view, the parameter effect of Example 27 is relatively better.
Claims
1. A composite fiber textile fabric, characterized in that: Calculated by mass percentage, it includes the following components: Nylon: 60-80%; Composite fiber: balance; The composite fiber is composed of modified polyester-cotton fiber and sea-island fiber in a mass ratio of 1:0.4-0.
6.
2. A composite fiber textile fabric according to claim 1, characterized in that: The preparation method of the modified polyester-cotton fiber is: The polyester-cotton fiber is immersed in a hydrogel precursor solution at a solid-liquid ratio of 1g:40-60mL, and the air pressure is reduced to 70-75kPa by vacuuming. The hydrogel precursor solution is heated to 85-95°C and maintained for 30-40min, and then the surface of the polyester-cotton fiber is subjected to corona treatment, wherein the irradiation temperature of the corona treatment is 20-40°C, the voltage is 15-25kV, the treatment time is 5-15min, and the distance between the electrode of the corona device and the polyester-cotton fiber is 0.5-4.5mm. After the corona treatment is completed, the polyester-cotton fiber obtained by the corona treatment is immersed in a sodium hydroxide solution with a mass fraction of 10-20% at a solid-liquid ratio of 1g:20-30mL, and the air pressure is further reduced to 10-20kPa by vacuuming. After maintaining for 5-10min, the polyester-cotton fiber is taken out and dried to obtain the modified polyester-cotton fiber.
3. A composite fiber textile fabric according to claim 2, characterized in that: The hydrogel precursor solution comprises, by weight, 15 to 20 parts of cellulose solution, 5 to 10 parts of antibacterial agent, 3 to 5 parts of nano zinc oxide and 8 to 10 parts of octadecanethiol.
4. A composite fiber textile fabric according to claim 3, characterized in that: The antibacterial agent is a silver ion antibacterial agent or a guanidine antibacterial agent, and the particle size of the nano zinc oxide is 40-50nm.
5. The method for preparing a composite fiber textile fabric according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Using the composite fiber as the core yarn and the nylon as the outer covering yarn in proportion to obtain a blended yarn, using the blended yarn as the warp and weft, and weaving the blended yarn to obtain a woven fabric at a warp density of 580 to 600 yarns / 10 cm and a weft density of 220 to 240 yarns / 10 cm; S2, dyeing the woven fabric and then setting it at 165-175° C. to obtain a set fabric; S3, padding the blank fabric twice in a photocatalyst hydrosol, performing a UV treatment in the first padding, the temperature of the photocatalyst hydrosol is 25-55°C, the rolling rate is 65-85%, the UV power is 500-600mW, and the second padding is performed in coordination with ultrasonic oscillation, the temperature of the photocatalyst hydrosol is 25-55°C, the rolling rate is 90-100%, and the ultrasonic oscillation frequency is 50-60KHz, to obtain a padded fabric; S4, drying and shaping the padded fabric at 100-115° C. for 5-10 min to obtain a textile fabric.
6. The method for preparing a composite fiber textile fabric according to claim 5, characterized in that: The photocatalyst hydrosol is a nano titanium dioxide aqueous solution with a concentration of 6-9 mg / L, wherein the particle size of the nano titanium dioxide is 5-10 nm.
7. The method for preparing a composite fiber textile fabric according to claim 5, characterized in that: After the padded fabric is obtained, electrostatic spraying of self-cleaning powder is performed from one side of the padded fabric toward the other side of the padded fabric, and the electrostatic spraying method is as follows: First, spray the first layer on the padding fabric, the spray width of the first layer accounts for 1 / 8 to 1 / 6 of the overall width of the padding fabric, and the length is the same as the overall length of the padding fabric, and then start from 20 to 30% of the width of the first layer, continue to spray the second layer, and then start from 20 to 30% of the width of the second layer, spray the third layer, until the entire padding fabric is sprayed; The spraying area of each layer is the same, and after each layer is sprayed, the sprayed padding surface is first heat treated at 100-120° C. for 20-30 minutes; In the electrostatic spraying, the distance between the spray gun and the impregnated fabric is 200-250 mm, the voltage is 60-70 kV, the current is 55-65 μA, the compressed air pressure is 0.2-0.4 MPa, and the spraying thickness is 45-65 μm.
8. The method for preparing a composite fiber textile fabric according to claim 7, characterized in that: The self-cleaning powder is composed of tourmaline negative ion powder, polycarbonate powder and silane coupling agent in a mass ratio of 1:0.4:0.2-0.3.
Citation Information
Patent Citations
Antibacterial textile and preparation method thereof
CN107938310A
Preparation method of anti-yellowing silver-containing dressing
CN109276747A
Processing technology of blended thermal insulation fabric based on tea carbon fibers and regenerated polyester fibers
CN116905158A
Improvements in or relating to the production of articles of regenerated cellulose
GB530619A
Fire Hydrant Pipeline Monitoring System
KR102623666B1